Electromagnetic Wave Theory and Applications - Kong, Jin Au; Ding, King Hau; Shin, Robert T.; Yang, Ying-Ching Eric; del Frate, Fabio; Sun, Liguo; Hsu, Chih-Chien; Johnson, Joel T.; Shih, Shih-En; Wang, Li-Fang; Zhang, Yan; Yeang, Chen-Pang; et al. (Research Laboratory of Electronics (RLE) at the Massachusetts Institute of Technology (MIT), 1995)
Contains table of contents for Section 3, reports on ten research projects and a list of publications. National Aeronautics and Space Administration Contract 958461 U.S. Navy - Office of Naval Research Grant N00014-92-J-1616 U.S. Navy - Office of Naval Research Grant N00014-89-J-1019 U.S. Navy - Office of Naval Research Grant N00014-90-J-1002 U.S. Army Cold Regions Research and Engineering Laboratory Contract PACA89-95-K-0014 Mitsubishi Corporation Agreement Dated 8/31/95 U.S. Navy - Office of Naval Research Grant N00014-92-J-4098 U.S. Federal Aviation Administration Grant 94-G-007 DEMACO Corporation Contract DEM-95-MIT-55 Joint Services Electronics Program Contract DAAH04-95-1-0038